Minstrelsy speaking: Metaparodic representations of blackface and linguistic minstrelsy in Hollywood films. (June 2018) - Lopez, Qiuana
Highlights: There are two components needed to ensure that neo-minstrelsy is considered metaparody rather than parody in Hollywood films. A black character is needed to critique, forgive, or authorize the blackface performance. The blackface character can take on the speaker role of animator and author, but not principle. Abstract: This article examines contemporary performances of blackface by fictional European American characters in three Hollywood films. The focus of analysis is the use of metaparody, or the parodying of a parody, and how this device problematizes White Hollywood representations of blackness while simultaneously reinforcing them. These metaparodic blackface performances also involve "linguistic minstrelsy, " a form of mock language that has existed since nineteenth-century minstrel shows, to construct Black identities for White characters. Linguistic minstrelsy in these films produces a jocularly oversimplified version of African American English. However, in these films, the linguistic and blackface minstrelsy are interpreted as humorous projections of incompetent white performances of blackness instead of merely parodies of African American language and culture for the following two reasons. First, the films include an "authentic" Black character who evaluates the performances for the audience. Second, the films limit the speaker roles for the blackface characters.